2004
DOI: 10.1080/01411920410001689706
|View full text |Cite
|
Sign up to set email alerts
|

Interactive whole class teaching in the National Literacy and Numercy Strategies

Abstract: The study set out to investigate the impact of the official endorsement of 'interactive whole class teaching' on the interaction and discourse styles of primary teachers while teaching the National Literacy and Numeracy Strategies. In both strategies, interactive whole class teaching is seen as an 'active teaching' model promoting high quality dialogue and discussion between teachers and pupils. Pupils are expected to play an active part in discussion by asking questions, contributing ideas and explaining and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 14 publications
8
74
0
8
Order By: Relevance
“…However, some authors, such as Smith et al (2004), have argued that 'interactive whole class' teaching strategies have not dramatically transformed traditional patterns of whole class interaction. Furthermore, Alexander (2004) suggests that the benefits of 'Dialogic Teaching' 11 will only be realised when teachers recognise that it: "…demands both pupil engagement and teacher intervention.…”
Section: Key Findings Exploredmentioning
confidence: 99%
“…However, some authors, such as Smith et al (2004), have argued that 'interactive whole class' teaching strategies have not dramatically transformed traditional patterns of whole class interaction. Furthermore, Alexander (2004) suggests that the benefits of 'Dialogic Teaching' 11 will only be realised when teachers recognise that it: "…demands both pupil engagement and teacher intervention.…”
Section: Key Findings Exploredmentioning
confidence: 99%
“…Other studies [5]- [7] prove that classroom discourse is limited to teacher-initiated questions are to a great extent display questions that are difficult to answer due to a short time allowed for response, and the third turn is merely a simple feedback.…”
Section: Classroom Discoursementioning
confidence: 99%
“…Cuban has demonstrated similar mismatches between reforming intentions and classroom practice during the 1920s and 1960s in the US (Cuban, 1993). More recently Smith et al (2004) reported that teachers in the UK over-estimated the extent to which they had changed their practice to enable more whole class interactive teaching, as demanded by government strategies. These two aspects of teacher conservatism are particularly apparent in circumstances where changes are imposed 'top-down' and are not necessarily carried through; perhaps if changes are developed 'bottom-up' through reflexive practice, it is more likely that teachers recognise that change is both possible and desirable.…”
Section: Introductionmentioning
confidence: 99%
“…This classroom arrangement developed in response to individualized learning and child-centred approaches popular in the 1960s and 1970s, but continues to be used, with some awkwardness, in classrooms where interactive whole-class teaching is now favoured (Smith et al, 2004;DfES, 2006).…”
Section: Introductionmentioning
confidence: 99%